A Review of Scenario Planning for Emissions in Environmental Assessments - Venmathy, Samanaseh; Zainura Zainon, Noor; Siti, Norasyikin; Che, Hafizan; Muhammad Amani, Mazlan; Florianna Lendai, Michael Mulok (Journal of Forecasting, 2022)
Various scenario classifications apply in attempts to make the field of future studies easier to outline. This paper discusses the appropriateness of various creating, coordinating, and consistency procedures for creating specific emission scenarios in environmental assessments. The Intuitive Logics, Story and Simulation (SAS), Social, Technological, Economic, Environmental and Political (STEEP), and La Prospective Models approaches are the five emission scenarios discussed in the paper analytically with their stages, storylines, steps, and building analysis. Every scenario method was examined and sorted into its separate benefits and limitations. Subsequently, the study selected the appropriate technique of emission scenario in environmental assessment with fulfilled scenario planning to deliver constructive scenarios. The study helps the upcoming designers by providing the fundamental direction on the extensive change towards a sustainable environment.